The Enhancement of Visible Absorption of Cu Doped ZnO Nanorods on Patterned Substrates - Tong, My Hoa; Lai, Thi Hoa; Minh Nguyen, Nhat; Ta, Thi Kieu Hanh; Pham, Thanh Tuan Anh; Huynh, Tran My Hoa; Tran, Cong Khanh; Phan, Bach Thang; Dang, Vinh Quang (VNU Journal of Science: Mathematics - Physics; Vol 37 No 1, 2021)
: We report the antireflection and light absorption in visible region by new stretchable substrates with patterned structure. Mogul substrates with 3-Dimentional structures were fabricated by using polydimethyl – siloxane that imitate the nanostructures surface. Then, Copper doped ZnO NRs on mogul-patterned surface by hydrothermal method at low temperature. The optical properties, morphology and structures of ZnO:Cu NRs were investigated through out of measurement the scanning electron microscopy, X-Ray diffraction and ultraviolet-visible spectroscopy, respectively. The results show the Cu doped ZnO NRs were uniformly and dense grown on mogul substrates, well oriented in the (002) plane. Additionally, the light absorption can be significantly enhanced to more 10% in a wide spectral range (400-800 nm) due to the reduce reflection. Growing ZnO NRs doping on new stretchable substrates with a mogul-patterned surface were successfully fabricated and applicable in the flexible and stretchable optoelectronic devices.